Responding to Social Change: Modern Social Teachings of the Moravian Church in North America - Atwood, Craig D. (Journal of Moravian history, 2025)
The Moravian Church has a long history of avoiding politics and social justice advocacy, but the 1957 General Synod encouraged provinces to be engaged in social justice and political issues. This article examines how the Moravian Church in North America addressed the social issues of the second half of the twentieth century. The 1986 Northern Province Synod is noteworthy because the province approved legislation addressing gender equality, sexuality, marriage, and family. It is noteworthy that the church focused on personal and domestic issues more than economic justice, climate change, domestic violence, police reform, or similar justice issues. But despite the increase in statements on a wide variety of social issues after 1957, we will see that the statements themselves tended to be equivocal. The issues that have animated delegates in synods dealt primarily with sexuality, personal morality, and family life for members of the church rather than social justice outside the church.